Dimensions of poverty in informal settlement: a case study of Disteneng Squatter Camp, Polokwane Municipality, Limpopo Province - Nkwinika, Zodwa (My University, 2007)
Apartheid land policy and its constitution as a whole conceptualized and structured South African in a way that encouraged inequalities in terms of land ownership, job opportunities and access to education and recreational facilities. The privileged few (whites and a few black elites and whosoever summarized with the former apartheid regime) got richer and richer while the less privileged people, (in this case, the majority of the black people of South Africa) got poor. They were even denied reasonable access to land and quality education. This investigative study examines the state in which they lived and how they are still living in Squatter Camp as an attempt to make qualitatively justifiable recommendations. Informal settlement is as old as the origin of urban settlement, which existed through industrialization process worldwide. A need for peace, jobs, security, housing and land ownership resulted in the establishment of informal settlement near big towns and mines. The most disadvantaged people, those characterized by poverty due to unemployment, lack of land ownership due to one reason or another move to informally settle nearer to areas in which there are possibilities for employment opportunities and better standard of living. Specifically, this study examines the deficiencies associated with the existing informal settlement through its assessment and evaluation. In this regard all aspects of assessment techniques of the way in which inhabitants of Disteneng informal settlement live i.e. interviewing processes (both structured and informal), observation through site visit, checking of documented information with regard to informal settlement etc have been used. The gaps that exist between urban life and the living conditions of people from squatter camp have been investigated and reflected.
Thesis (M. Dev.) --University of Limpopo, 2007.
Keywords: Poverty; Informal settlements; Poverty -- South Africa -- Limpopo; Squatter settlements; South Africa -- Social conditions; South Africa -- Economic conditions